Hubungan Ketuban Pecah Dini, Partus Lama, dan Gawat Janin dengan Tindakan Persalinan Sectio Caesarea di Rumah Sakit TK. IV DR. Noesmir Baturaja Tahun 2020 - Yuhana Yuhana; Tuti Farida; Turiyani Turiyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Sectio Caesarea is an artificial birth, in which the fetus is born through an incision in the abdominal wall and uterine wall with the condition that the uterus is intact and the fetal weight is above 500 grams. According to WHO, national rate of cesarean delivery does not exceed 10% of all births. The mortality rate due to Sectio Caesarea delivery ranges from 40-80 people per 100,000 live births. This study aimed to determine the relationship between premature rupture of membranes (PROM), Prolonged labor, and fetal distress with Sectio Caesarea delivery at Level IV hospital of Dr. Noesmir Hospital, Baturaja in 2020. It was an analytic survey with cross sectional approach. The population in this study was all mothers giving birth at Level IV Hospital of Dr. Noesmir Hospital, Baturaja in 2020 with a total of 332 people. 77 samples were selected using Systematic Random sampling technique. The data were analyzed using Chi Square statistical test. The results showed that the factors associated with caesarean section delivery were premature rupture of membranes with a p-value = 0.028 (≤ 0,05), fetal distress with a p-value = 0.029 (≤ 0,05), whereas the factor that is not related to it was prolonged labor a p-value = 1.000 ( > 0.05). This study can be used as a reference to add insight and skills for readers and a reference to improve the quality of services in hospitals.